The Association between Social Engagement, Social Network, Social Embeddedness and Quality of Life among University Students - Abdullah, Mohd Zulkifli; Mohamad Yunus, Noor’ain; Anuar, Annurizal; Abdul Rashid, Mas Anom; Lipa , Michelle; Yao, Geng (Information Management and Business Review, 2024)
Quality of life (QoL) among university students is a critical concern that impacts not only their academic success but also their overall well-being and prospects. Social relationships are critical for university students’ quality of life. Positive social interactions and a supportive network can enhance students’ sense of belonging and emotional well-being. However, many students struggle with loneliness and social isolation on campus. This study aims to investigate the association between civic engagement (social engagement, social network, and social embeddedness) and the QoL among university students. We conducted this cross-sectional study among 179 university students on the UiTM Puncak Alam campus via an online survey. We adapted the questionnaire from previous studies and used SPSS version 29 to analyze the data. The Pearson correlation test revealed a link between all the independent variables and the dependent variable, demonstrating both convergent and concurrent validity. The regression analysis showed that social embeddedness was the best predictor of QoL, followed by attitude and behavior. A secure social environment can help one adapt more effectively and provide emotional support, which lowers the risk of depressive symptoms and improves the QoL. In addition, active involvement in social activities helps to increase the sense of belonging to the university community. Identifying oneself as a member of a group of peers, faculty, and staff contributes to the student’s self-concept and higher self-esteem, which is vital in terms of psychological health and QoL.